The impacts of port infrastructure and logistics performance on economic growth: the mediating role of seaborne trade - Ziaul Haque Munim; Hans-Joachim Schramm (Journal of Shipping and Trade (JST), 2018)
Considering 91 countries with seaports, this study conducted an empirical inquiry into the broader economic contribution of seaborne trade, from a port infrastructure quality and logistics performance perspective. Investment in quality improvement of port infrastructure and its contribution to economy are often questioned by politicians, investors and general public. A structural equation model (SEM) is used to provide empirical evidence of significant economic impacts of port infrastructure quality and logistics performance. Furthermore, analysis of a multi-group SEM is performed by dividing countries into developed and developing economy groups. The results reveal that it is vital for developing countries to continuously improve the quality of port infrastructure as it contributes to better logistics performance, leading to higher seaborne trade, yielding higher economic growth. However, this association weakens as the developing countries become richer.
Keywords: 650; international trade; economic growth; developing economies; structural equation modeling; multi group analysis; neoclassical growth theory; liner shipping connectivity